Sistem Perkawinan dan Pewarisan pada Masyarakat Hukum Adat Rejang Provinsi Bengkulu - Arso, Dimas Dwi; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
This study aims to find out the marriage and inheritance system in the Rejang Customary Law community of Bengkulu Province. This research is descriptive analysis. In this study will describe and analyze the marriage and inheritance system of the Rejang Customary law community in Bengkulu Province. This study uses a normative approach, which is done by conducting a study of library materials both primary, secondary and tertiary legal materials in order to obtain answers about marriage and inheritance to the Rejang Customary law community. The data obtained in this study analyzed by using qualitative analysis and the output is descriptive analysis data, in this study qualitative analysis was carried out with inductive deductive thinking methods and vice versa to describe the marriage and inheritance system of the Rejang Customary law community in Bengkulu Province. Research results show that for the rejang tribe, the marriage ceremony is a place to show strength (both wealth and the large number of families) as well as a sign of sanctity. The marriage ceremony is the last ceremony held by parents towards each of their children. It could also be said to be a ceremony of